Jab - Halliday, Mark, 1949- (Phoenix poets., 2002)
Human, hunger, happiness, hope, heart, and Halliday all start with h, as does ham. Accident? Maybe! But seldom have the flour of the humanistic and the egg yolk of honesty mixed more swellingly with the yeast of desire and the salt of self-doubt-not to mention the olive paste of ambition.Halliday has whacked Death and Mutabilitie before, but this time . . . this time he whacks them again. After this Jab, the world will never be the same. Or at least, a few hundred conversations, here and there, will be somewhat affected. Roll over Death, and tell Mutabilitie the news.